Artificial immune system agent model - Che Doi, Siti Mazura; Md Norwawi, Norita (2011)
The Artificial Immune Systems (AIS) is a biologically inspired techniques that emulates a natural system, in particular the vertebrate immune system, in order to develop computational tools for solving engineering problems.Immunity-based technique emerge as a new branch of artificial intelligence (AI).The human biological immune system has become the source of inspiration for developing intelligent problem-solving techniques.The powerful information processing capabilities of the human system, such as feature extraction, pattern extraction, learning, memory and its distributive nature provide rich metaphors for its artificial counterpart. Hence, the goal of this study is to develop an Artificial Immune System (AIS) model using agent approach for incremental learning.The main issue handled was how to integrate a multiagent system into an AIS application.This model proposed was simulated using cases for the performance measurement.The step by step activities performed in developing the agent based AIS model can be a guideline in developing an AIS application. Besides that, the simulation of the AIS model can be further enhanced to be used for teaching and learning purposes.